EVALUASI KEGIATAN KELOMPOK KERJA GURU (KKG) PAI DI KECAMATAN PAGAR JATI KABUPATEN BENGKULU TENGAH - Salimah Salimah (UIN Fatmawati Sukarno Bengkulu, 2020)
Abstract: The problems in this study were 1) How is the evaluation of the activities carried out by teachers working group (KKG) of religious education, 2) How to Evaluate Activity of teachers working group (KKG) of religious education on the skills of teachers in teaching in the District Pagar Jati Central Bengkulu, 3) Obstacles and supporting teachers to follow the activities of teachers working group (KKG) of religious education. The method used in this research is qualitative research to uncover these problems in depth and thorough, while informants studied were administrators and members of the working group of religious education teacher residing in District Jati fence. Results of this research are activities by the working group of teachers in the district teak Fences routine nature there is no regular monthly as well when there are things that should be important if it can be weekly Mass will face semiannual then we will discussion to discuss the matter grating, preparation of RPP which will be given to students, or the Mass there is an urgent problem that must be solved together. Later in the activities of the working group also conducted seminars for teacher’s workshop of the religious education and other activities to increase knowledge and skills for the Master of religious education. Work activities teachers can help teachers’ skills in teaching activities of teachers working groups in the district of religious education teak railings so help teachers, because this activity is aimed to help teachers of religious education to be more proficient and professional in teaching, this activity is usually held one month one month 2 times, or if there are urgent as the new school year can be activities once a week.In carrying out the activities of the working group of teachers in the district Pagar Jati no problems were severe constraints only a little too did not become an obstacle in these activities.